THE EFFECT OF POE (PREDICT-OBSERVE-EXPLAIN) LEARNING MODEL ON LEARNING OUTCOMES AND STUDENT RETENTION ON PLANT TISSUE - Nia Amriza Sagala; Hudson Sidabutar; Mike Stavsley Tanjung (Jurnal Pelita Pendidikan, 2021)
This study aims to determine the effect of the POE learning model on student learning outcomes and retention. This study uses a quantitative approach with a pre-test, posttest, and retest design. The type of research used is a quasi-experimental research with a research sample of class XI students at SMA Negeri 1 Aek Natas in the 2020/2021 learning year. The sampling technique used simple random sampling. The data analysis technique used is to test the hypothesis using the T-test at a significant level of α = 5%. If the price of the F-count is greater than Ftable, then H0 is rejected, and Ha is accepted. Learning outcomes are measured by giving a posttest to students, while retention is measured by providing a retest for 14 days two times. The mean of learning outcomes in the experimental class was 83.88, while the mean learning outcomes in the control class were 78 so that there was a difference in learning outcomes between the control class and the experimental class by 5.88 points. The average retention 1 in the experimental class was 97.07%, while the average retention 1 in the control class was 88.06%, so that there was a point difference of 9.01%. The second retention means results in the experimental class obtained 95.77%, while in the control class, it was 79.53% so that there was a point differential of 16.24%. The experimental class decreased retention points 1 to 2 by 1.3% and for the control class by 8.53%. This study indicates that there is an effect of the POE (Predict-Observe-Explain) learning model on student learning outcomes and retention of plant tissue material.